Silver Nanoparticles Coated Poly(L-Lactide) Electrospun Membrane for Implant Associated Infections Prevention - Wang, Jiaolong; Zhan, Lilin; Zhang, Xianhua; Wu, Runfa; Liao, Lan; Wei, Junchao (Frontiers in Pharmacology, 2020)
Bacterial infection has been a critic problem for implant infections. Poly(L-lactide) (PLLA) membrane has great potential for Guided bone regeneration (GBR), however, PLLA lack antibacterial properties and thus may face bacterial infections. In this work, a mussel inspired method was used to treat PLLA membrane with dopamine and formed poly(dopamine) (PDA) coated PLLA(PLLA@PDA), and then silver Nanoparticles (AgNPs) was immobilized on the surface of PLLA via the reduction effect of PDA. The antibacterial test showed that the Ag NPs coated PLLA (PLLA@Ag) have good antibacterial properties, besides, the composite membrane have good biocompatibility, implying that the PLLA@Ag membrane have potential applications as antibacterial GBR membrane.